2018
DOI: 10.1088/1741-4326/aaf01d
|View full text |Cite
|
Sign up to set email alerts
|

Helically localized ballooning instabilities in three-dimensional tokamak pedestals

Abstract: Recent experimental observations have found toroidally localized MHD instabilities in the plasma edge during operation with applied magnetic perturbations on ASDEX Upgrade in H-mode with low collisionality (ν ≈ 0.4). Large edge plasma displacements are induced by a stable kink response to the 3D magnetic perturbations. This kink response results in localized changes of geometric quantities, which in turn leads to the localization of MHD instabilities in the plasma edge. Infinite-n ideal MHD ballooning theory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The inclusion of more toroidal modes resulted in further destabilisation and stronger poloidal localisation of the peeling-ballooning mode. The strong poloidal and field-line localisation in 3D geometry is a feature that is observed experimentally in AUG in cases of ELM mitigation [18], and was successfully reproduced by theory based on a local ballooning analysis [17]. In those cases the 3D ballooning mode was localised around specific field lines, that coincided with locations where the plasma response crosses zero, i.e.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The inclusion of more toroidal modes resulted in further destabilisation and stronger poloidal localisation of the peeling-ballooning mode. The strong poloidal and field-line localisation in 3D geometry is a feature that is observed experimentally in AUG in cases of ELM mitigation [18], and was successfully reproduced by theory based on a local ballooning analysis [17]. In those cases the 3D ballooning mode was localised around specific field lines, that coincided with locations where the plasma response crosses zero, i.e.…”
Section: Discussionmentioning
confidence: 60%
“…In particular, the imposed 3D fields lead to local changes of plasma equilibrium parameters, that play a crucial role in determining the stability of the plasma. This leads to the destabilisation of high n 4 ideal ballooning modes, where n is the toroidal mode number of the perturbation, which is localised about the most unstable magnetic field lines [15][16][17]. Such a feature is computationally and experimentally observed in ASDEX Upgrade (AUG) discharges, when ELM mitigation occurs [18].…”
Section: Introductionmentioning
confidence: 99%
“…The measured corrugation compares well to the displacement of the 3D VMEC equilibrium normal to the axisymmetric equilibrium ξ n (VMEC). Linear ideal ballooning theory shows a mode on the field line region that is least stable against field line bending due to the 3D corrugation [66,67]. Measurements of T e and n e perturbations with a new fast He beam diagnostic [68] show neither a phase delay between T e and n e oscillation nor an inversion radius as expected for an island (see figure 9).…”
Section: No Elm Regimes and 3d Perturbationsmentioning
confidence: 93%
“…Experimental observations showed that the application of a MP field causes inter-ELM modes and the ELM onset to appear in certain helical positions (at certain toroidal phase angles) instead of being randomly located along the toroidal direction [10]. The toroidal mode localization for infinite-n ballooning modes, which are located at a single flux surface, was studied analytically by [11]. The helical localization of intermediate to high toroidal mode number peeling-ballooning modes in non-axisymmetric tokamak plasmas in the limit of weak MP fields (perturbative stability analysis) was investigated by [12].…”
Section: Introductionmentioning
confidence: 99%